A theoretical study on the hydrogen transport mechanism in SrTiO3 perovskite. II. Scandium doping at titanium site. Issue 4 (29th March 2012) - Onishi, Taku; Helgaker, Trygve; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Hybrid Kohn–Sham calculations are performed to clarify the proton‐conduction mechanism in Sc‐doped SrTiO3 perovskite, from the viewpoint of energetics and bonding. The calculated potential energy curves are discussed and a molecular‐orbital analysis performed. Much hydrogen can exist around doped scandium, where it is energetically stabilized. However, scandium‐doping has no energetic advantage in the activation energy for proton‐conduction. © 2012 Wiley Periodicals, Inc.